2006
DOI: 10.1002/cncr.21935
|View full text |Cite
|
Sign up to set email alerts
|

Gum mastic inhibits the expression and function of the androgen receptor in prostate cancer cells

Abstract: Accumulating evidence suggests that the androgen receptor (AR) may play an important role in the development and progression of prostate cancer. To find new, useful compounds that effectively may attenuate the function of AR in prostate cancer cells, the authors investigated the effect of gum mastic, a natural resin, on AR activity. An androgen-responsive prostate cancer cell line LNCaP was used as a model for this study. Gene transfer, reverse transcriptase-polymerase chain reaction analysis, electrophoretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
(48 reference statements)
3
44
0
2
Order By: Relevance
“…They concluded that the ethanol-terpene-rich extract was the most effective. A similar mechanism was observed in prostate cancer cells (He et al, 2006;He et al 2007aHe et al , 2007b.…”
Section: Chios Mastic (Pistacia Lentiscus L) and Cancer Chemopreventionsupporting
confidence: 77%
See 1 more Smart Citation
“…They concluded that the ethanol-terpene-rich extract was the most effective. A similar mechanism was observed in prostate cancer cells (He et al, 2006;He et al 2007aHe et al , 2007b.…”
Section: Chios Mastic (Pistacia Lentiscus L) and Cancer Chemopreventionsupporting
confidence: 77%
“…5 g/day/person (Triantafyllou et al, 2007), 4 g/day/person (Bebb et al,2003), 2.2 g/day/parson (Kaliora et al, 2007a(Kaliora et al, , 2007b, or 1 g/day/person (Al-Habbal et al, 1984). Favorable effects of mastic such as anticarcinogenic potential could be achieved at relatively low doses without any toxicity (He et al, 2006). Further studies must elucidate the mechanisms underlying and determine safety levels in humans.…”
Section: Chios Mastic (Pistacia Lentiscus L) and Cancer Chemopreventionmentioning
confidence: 99%
“…The antitumor activity of a drug is associated with inhibition of tumor cell proliferation, promotion of cellular differentiation, and induction of apoptosis. Gum mastic is a natural extract of Pistacia lentiscus trees, and its anticancer properties are newly identified [16][17][18]22] . In vitro, gum mastic has been proven to inhibit growth of prostate cancer cells and induce apoptosis of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For semiquantitative RT-PCR, Tag DNA polymerase was used in the reaction system. Primer sequences for AR (He et al 2006) and GAPDH were synthesized from published sequences as shown in Table 2.…”
Section: Rna Isolation and Pcrmentioning
confidence: 99%